Metadherin Promotes Malignant Phenotypes And Induces Beta-Catenin Nuclear Translocation And Epithelial–Mesenchymal Transition In Gastric Cancer - Feng, Di (Cancer Manag Res, 2019)
PURPOSE: Metadherin (MTDH), as an oncogene, is associated with metastasis and poor prognosis. This study investigated MTDH expressions and development of gastric cancer (GC) cell phenotypes and the contribution of MTDH to epithelial–mesenchymal transition (EMT). PATIENTS AND METHODS: MTDH expression was assayed in human GC cell lines and tumor tissue from 92 GC patients. Functional experiments were performed to characterize MTDH activity. Expressions of EMT-related proteins (vimentin and E-cadherin), phosphorylated β-catenin and β-catenin were assayed by immunohistochemistry, Western blotting, immunofluorescence, and co-immunoprecipitation, respectively. RESULTS: MTDH expressions were higher in GC tissue than that in gastric mucosa from the same patient. MTDH overexpression was correlated with metastasis and enhanced malignant GC phenotypes, i.e., proliferation, migration, invasiveness, and chemoresistance. MTDH overexpression was associated with expressions of vimentin, E-cadherin and cancer stem-cell biomarkers including CD44, CD133, and Oct4. MTDH complexed with β-catenin and decreased phosphorylated β-catenin levels to facilitate β-catenin translocation into the nucleus and expressions of downstream genes. CONCLUSION: MTDH overexpression in GC cells is associated with EMT and development of cancer stem cell malignant phenotypes and affects the subcellular translocation of β-catenin. The results warrant investigation of the prognostic value of MTDH in GC and as a therapeutic target.